Interventions for Students with Problem Behaviors: A Workshop Incorporating Applied Behavior Analysis for Japanese Teachers - Inoue, Masahiko (Yonago Acta Med, 2021)
BACKGROUND: We conducted a workshop-style program based on applied behavior analysis (ABA) for Japanese teachers in charge of children with developmental disabilities who had behavioral problems. Additionally, we investigated whether making and implementing behavioral intervention plans (BIPs) for participants, improved students’ behavioral problems, and the mental health of participants. METHODS: The participants were 18 Japanese elementary and kindergarten teachers in charge of students with behavioral problems. The workshop comprised eight two-hour sessions of lectures and group discussions related to ABA. Achievement level was evaluated for the development and implementation of the BIP and improvement of behavioral problems. In addition, we analyzed changes in the 30-item General Health Questionnaire (GHQ-30) scores pre- and post-workshop to assess participants’ mental health. Fifteen teachers who participated in more than half of the sessions were analyzed. RESULTS: All 15 teachers analyzed were able to perform appropriate functional behavioral assessment (FBA) and make a BIP, and 12 showed improvement in the targeted problem behaviors. Many target behaviors had avoidance functions and many antecedent strategies were behavior contracts. Adaptive behaviors incompatible with problem behaviors were selected as alternative behaviors to problem behaviors. Also, there was no aversive control over the outcome strategy. The average score for “social activity disorder” and “anxiety / caprice” in GHQ30 showed a statistically significant improvement in pre- and post-workshop. CONCLUSION: It was found that appropriate FAB and BIP could be created using “the strategy sheet,” in workshops based on the ABA. It was also suggested that the workshop program may in turn improve teachers’ mental health. Further study is needed on the effectiveness of the workshop program using intergroup comparison designs for more subjects.